The legacy of redlining in the effect of foreclosures on Detroit residents' self-rated health. (January 2019) - McClure, Elizabeth; Feinstein, Lydia; Cordoba, Evette; Douglas, Christian; Emch, Michael; Robinson, Whitney; Galea, Sandro; Aiello, Allison E.
Abstract: Historical practices, such as housing discrimination in Detroit, have been shown to have lasting impacts on communities. Perhaps the most explicit example is the practice of redlining in the 1930s, whereby lenders outlined financially undesirable neighborhoods, populated by minority families, on maps and prevented residents from moving to better resourced neighborhoods. Awareness of historical housing discrimination may improve research assessing the impacts of current neighborhood characteristics on health. Using the Detroit Neighborhood Health Study (DNHS), we assessed the association between two-year changes in home foreclosure rates following the 2007–2008 Great Recession, and residents' five-year self-rated health trajectories (2008–2013); and estimated the confounding bias introduced by ignoring historical redlining practices in the city. We used both ecological and multilevel models to make inference about person- and community-level processes. In a neighborhood-level linear regression adjusted for confounders (including percent redlined); a 10%-point slower foreclosure rate recovery was associated with an increase in prevalence of poor self-rated health of 0.31 (95% CI:−0.02 to 0.64). At the individual level, it was associated with a within-person increase in probability of poor health of 0.45 (95% CI:0.15–0.72). Removing redlining from the model biased the estimated effect upward to 0.38 (95% CI:0.07–0.69) and 0.56 (95% CI:0.21–0.84) in the neighborhood and individual-level models, respectively. Stratum-specific foreclosure recovery effects indicate stronger influence in neighborhoods with a greater proportion of residents identifying as white and a greater degree of historic redlining. These findings support earlier theory suggesting a historical influence of structural discrimination on the association between current neighborhood characteristics and health, and suggests that historical redlining specifically may increase vulnerability to contemporary neighborhood foreclosures. Community interventions should consider historical discrimination in conjunction with current place-based indicators to more equitably improve population health. Highlights: Slower post-Recession neighborhood foreclosure recovery is associated with worse self-rated health in Detroit. Neighborhood history of redlining contributes substantially to the association between foreclosure recovery and self-rated health. Historical discriminatory practices should be considered when designing community interventions to improve population health and health equity.